Analysis of Functional Capacity and Endurance on Women Futsal Athletes In Sleman Regional Sports Week (Porda) - Ummy A'isyah Nurhayati; Nindy Suci Dameyla (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2022)
Along with the ability to grasp technique, tactics, and mental toughness, physical condition is one of the crucial components or aspects to success in sports. The survey conducted showed that the experience of athletes who often experience fatigue, most of them do not have a good physical condition background, especially the endurance component, athletes often experience fatigue and gasping for breath during the match. This condition is closely related to functional capacity and endurance. If the functional and endurance are not trained properly, it can interfere with the athlete's performance and have an impact on the achievements of the sports club. This study aims to analyze the functional capacity and endurance of the female Futsal athlete Porda Sleman. This study uses a quantitative descriptive method by studying the dynamics of the correlation between risk factors and effects and this study uses a point time approach design through observation or data collection at one time, meaning that each research subject is only observed once, and measurement of status, character, subject variable is done at the same time. This study shows that the majority of female players in the female utsal Porda Sleman have VO2Max in the excellent category as many as 9 respondents (47.4%). A high VO2Max or in a good category is an indicator of aerobic fitness, heart health and endurance performance